Human Being in the Dimension of the Psychosociocultural Matrix of Philosophizing - Karpenko, I. V.; Guzhva, A. A. (Anthropological Measurements of Philosophical Research, 2021)
Purpose. The article highlights the demand for critical thinking in everyday life at the present stage of development of globalized culture and emphasizes the role of philosophy as a source of rationality. Philosophizing, which is determined by the psychosociocultural matrix, sets the toposes, vocabulary and rhythms of meaning making, their preservation and transformation. The purpose of the article is to concretize the practices of socio-cultural communication, primarily through the social institute of education, where individuals interact with the psychosociocultural matrix of philosophizing, which mediate the general and individual level in philosophical culture. Theoretical basis of the study are cultural anthropology and phenomenological methods. Originality of the study: based on the philosophy of intersubjectivity, we actualized the rational grounds for formation of adequate judgments in modern culture at the level of everyday life. This justifies the inevitability of the spread of various forms and types of philosophical education, philosophical thinking, ideas and values developed in philosophical communities beyond the narrow circle of professional philosophers. This implies the systemic involvement of philosophers as professionals of meaning-making in solving problems in various non-academic fields – politics, economics, law, etc. The formation of skills of philosophical critical thinking in the process of preparing young people for active civil life is no less important aspect of this. Conclusions lead to an understanding of the existential importance of philosophy and philosophizing and the need for organized forms of knowledge transfer such as the Faculty of Philosophy of the Classical University. There is a mutual interest and interaction of the general culture of society and philosophy as a special kind of culture. Because philosophy actively configures other forms of culture, contributes to the creation of sociocultural identities precisely because of its ability to conceptually reproduce the core of the psychosociocultural matrix that underlies the existence of all these different forms within one society. The sociocultural macro level of philosophical spiritual practices is formed by the psychosociocultural matrix of the philosophical tradition, which retains its longevity from the emergence of philosophy and goes through its history, demonstrating the features of the national reception of philosophy as a national-specific embodiment of sociocultural macro level of the psychosociocultural matrix.